2013
DOI: 10.3354/dao02577
|View full text |Cite
|
Sign up to set email alerts
|

Validating the identity of Paramoeba invadens, the causative agent of recurrent mass mortality of sea urchins in Nova Scotia, Canada

Abstract: Green sea urchins Strongylocentrotus droebachiensis along the coast of Nova Scotia, Canada, suffer mass mortalities from infection by the pathogenic amoeba Paramoeba invadens Jones, 1985. It has been speculated that P. invadens could be a form of Neoparamoeba pema quidensis, a species associated with disease in S. droebachiensis and lobsters in the northeast USA. During a disease outbreak in fall 2011, we isolated amoebae from moribund urchins collected from 4 locations along ~200 km of coastline. In laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 59 publications
4
65
1
Order By: Relevance
“…Therefore, those authors argued that Neoparamoeba branchiphila (which has recently been sug gested as Paramoeba branchi phila comb. nov. based on evidence from analysis of SSU rDNA; Feehan et al 2013) either caused the observed disease in D. africanum or contributed to it. Considering this previous information, our study supports the hypothesis that the amoeba N. branchiphila may play an opportunistic role, given that experimental injection of V. alginolyticus caused disease symptoms in D. afri ca n um.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, those authors argued that Neoparamoeba branchiphila (which has recently been sug gested as Paramoeba branchi phila comb. nov. based on evidence from analysis of SSU rDNA; Feehan et al 2013) either caused the observed disease in D. africanum or contributed to it. Considering this previous information, our study supports the hypothesis that the amoeba N. branchiphila may play an opportunistic role, given that experimental injection of V. alginolyticus caused disease symptoms in D. afri ca n um.…”
Section: Discussionmentioning
confidence: 99%
“…Disease outbreaks in Nova Scotia have been linked to storm activity and warm water temperatures and are becoming increasingly more frequent (Scheibling & Lauzon-Guay 2010, Scheibling et al in press). Con sequently, kelp beds currently dominate much of the Nova Scotian coast, although barrens exist locally along headlands off central Nova Scotia and the southwestern shore (Feehan et al 2013). …”
Section: Barrens In Regions With Documented Multiple Phase Shiftsmentioning
confidence: 99%
“…For many of these disease events, a causative pathogen remains undescribed which severely limits the study of the ecology and evolution of infectious diseases of these animals. Of the cases in which a pathogenic agent has been identified or statistically associated with a disease, bacteria and eukaryotic parasites (amoebozoa) are the most well described [5,6]. To date, no fungi have been found associated with echinoderm disease and viruses have only recently been explored as potential pathogens [7].…”
Section: Introductionmentioning
confidence: 99%